Safety and efficacy of l‐arginine produced by fermentation with Corynebacterium glutamicum KCCM 80182 for all animal species. (2nd May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐arginine produced by fermentation with a genetically modified strain of Corynebacterium glutamicum KCCM 80182 when used as a nutritional additive in feed and water for drinking for all animal species categories. Viable cells of the production strain and its recombinant DNA were not detected in the additive. The product l ‐arginine, manufactured by fermentation with C. glutamicum, KCCM 80182, does not give rise to any safety concern with regard to the production strain. l ‐Arginine produced using C. glutamicum KCCM 80182 is considered safe for the target species. The FEEDAP Panel has concerns regarding the safety of the simultaneous oral administration of l ‐arginine via water for drinking and feed. l ‐Arginine produced using C. glutamicum KCCM 80182 is safe for the consumer and for the environment. The additive is not hazardous by inhalation, is not a skin sensitiser, but is corrosive to skin and eyes. The product under assessment is considered an efficacious source of the amino acid l ‐arginine for all animal species. For l ‐arginine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against microbial degradation in the rumen.